Barriers and opportunities for the access to health services according to the experience of children and teenagers with cancer carers - Ávila Mora, Juan Carlos
Child cancer is a pathology with multiple primary triggers, and it is related with health determiners, where service access and financial risk protection assurance are relevant aspects for early diagnostic, management and treatment of illnesses. A research for analyzing both barriers and opportunities for accessing to the health services was brought up according to the experience of care providers that support the cancer control in children and teenagers in Colombia, through a study of qualitative focus and interpretative hermeneutic design comprising nine focal groups in 36 children carers who look after children diagnosed with cancer in different foundations in four cities in Colombia (Cali, Cartagena, Medellín and Santa Marta). The data was analyzed in the Nvivo program and the obtained information was codified to create in total five categories of analysis and their respective subcategories: 1. Availability of services; 2. Physical, organizational and financial accessibility; 3. Services acceptability; 4. Contact with the service and 5. Access opportunities. It was found that the main barriers are related with the access to health services and the administrative processes related to the same, difficulties with the treatment continuity because of a lack of ways to perform it, that leads to the use of legal resources. It is evident that a change in the lifestyles of the main carers that also impacts the family core on its multiple dimensions as most of the members of this have to modify their routines. It is also laid out that patients with this kind of pathologies that are in a differential path of attention in the health services allowing to perform early diagnoses and an adequate continuity of the treatment.